Effects of Feeding Silage of Napier Pakchong 1 Fermented with Mung Bean Concentrate on Production Performance, Nutrient Digestibility, Carcass Yield and Meat Quality of Male Dairy Goat - Achara Lukkananukool; Jamlong Mitchaothai; Supapun Boonkoed; Ronachai Sitthigripong; Chunya Kongrith; Nahathai Vijitrothai; Thanatsamonwan Phonmun (My University, 2023)
The current study aimed to investigate the effects of feeding silage of Napier Pakchong 1 fermented with mung bean concentrate on production performance, nutrient digestibility, carcass yield, and meat quality of male dairy goats. Silage made for experimental treatments was prepared as follows: Treatment 1 (T1) containing 100% Napier Pakchong 1 grass (without mung bean concentrate added) as a control, while Treatment 2 (T2) and Treatment 3 (T3) containing 90% and 80% Napier Pakchong 1 grass, respectively, mixed with 10% and 20% mung bean concentrate, respectively. Fifteen weaned male Saanen-growing goats were assigned to 3 experimental treatments in a completely randomized design; the study lasted for 150 days. The nutritive value of feed, production performance, nutrient digestibility, blood urea nitrogen, carcass yield and dressing, basic meat quality, and composition of meat were collected or analyzed. The results found that the goats fed with the silage made from Napier Pakchong 1 added 10% and 20% mung bean concentrate showed improvements in nutritive value, growth rate, key nutrient digestibility, blood urea nitrogen, carcass yield, the water-holding capacity of cooked meat, and fat content in meat. However, adding 10% mung bean concentrate had a trend of more beneficial value added into the production chain of male Saanen dairy goats for meat purposes. Thus, silage made from Napier Pakchong 1 fermented with 10% mung bean concentrate as a roughage source for male Saanen dairy goats intended for meat purposes is recommended.
Keywords: Silage; Food Quality and Safety Studies